Medullary Position at the Craniocervical Junction in Mature Cavalier King Charles Spaniels: Relationship with Neurologic Signs and Syringomyelia. (30th April 2015) - Cerda‐Gonzalez, S.; Olby, N.J.; Griffith, E.H.
<x xml:space="preserve">Abstract</x> Background Medullary elevation (ie, medullary kinking) at the craniocervical junction (CCJ) is reported in dogs with Chiari‐like malformations (CM), but its diagnostic criteria and clinical relevance are unclear. Objective To describe the position of the medulla at the CCJ in mature cavalier King Charles spaniels (CKCS), and evaluate its relationship with clinical status and the presence of syringomyelia. Animals Thirty‐six CKCS, 5–12 years of age, including 16 asymptomatic dogs. Methods Dogs were assigned a neurologic grade; magnetic resonance imaging (MRI) of the CCJ then was performed. The presence of a CM and syringomyelia was recorded and syringomyelia severity was quantified. Medullary position was quantified using the medullary kinking index, the elevation angle and obex position relative to the foramen magnum. The relationship between medullary position measures and presence and severity of neurologic signs and syringomyelia was investigated. Results Chiari‐like malformation was found in 33 dogs; 26 of them had syringomyelia. Mean medullary kinking index was 46.4% (SD, 10.3), elevation angle was 132° (SD, 12) and obex position was 3.5 mm (SD, 0.8). A higher medullary kinking index was associated with the presence of neurologic signs (P = .0368). Obex position was associated with the presence (P = .0018) and severity of syringomyelia (P = .0164). Conclusions and clinical importance There is a significant association between medullary elevation and clinical signs, whereas more caudal brainstem positions appear related to the presence of syringomyelia.